Integrating lessons from the Qur’an and Hadith in teaching Molecular biology - Rahman, Mohammad Tariqur (Kulliyyah of Science, IIUM, 2011)
The integration of the teachings of Islam in many fields of studies such as physics, chemistry, mathematics, engineering, and molecular biology is perceived by many to be easier said than done. However, it is necessary to caution that taking teachings from Islamic guidelines and integrating them to the context of scientific evidence or vice versa poses inherent threats of inconsistency and inaccuracy. The number of verses in the Qur’an and the number of authentic narrations of hadith are restricted; however, the interpretations and the subsequent understanding of those are diverse. Hence, it is not unlikely that understanding of one aspect or issue by one individual may differ from the understanding of the same issue by another. Furthermore, the wisdom of Allah (s.w.t), the All Knower who revealed the Qur’an to mankind is absolute compared to the limited human knowledge the basis of most of the scientific theories. At the same time, difference of opinions or controversies among different groups of scientists also exists in explaining a theory of a scientific observation or its application. Therefore, under no circumstances should such integration be aimed at validating or promoting the teachings from Qur’an and hadith using scientific theories. This paper highlights few possible ways to integrate lessons from Islam while teaching Molecular Biology. However, it is hoped that the paper would open new ideas to integrate lessons from Islam with course/topic of interests. The focus of the field of molecular biology includes structure function and mechanisms of actions of macromolecules or biomolecules such as proteins, carbohydrates, lipids and nucleic acids (DNA and RNA) found in living things. Relating an understanding of certain verses from the Qur’an and teachings from hadith this paper addresses the issues on (i) isomeric preference in structure of biomolecules (ii) application of molecular biology for genetic modification of animals and plants (iii) application of molecular biology as therapeutic interventions and (iv) use of molecular biology in manipulating living processes and/or to create life.